Analisis Kinerja XBee Seri 2C Berdasarkan Jarak dan Besar Paket Data - Ayu Dewi Khumairoh; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The choice of transmission devices in the technology of the Wireless Sensor Network (WSN) is very important. At present one of the problems that is still being examined in WSN technology research is the speed of data transmission. Because the energy requirements used by the system are getting smaller, it will result in more data transmission. To overcome this problem, a low-power RF XBee S2C device is chosen but data transmission performance is better. By analyzing the throughput value and Range-test analysis to find RSSI values ​​and the percentage of data sent, XBee S2C was tested with a variety of test distance traveled scenarios, namely 10 meters to 400 meters, and variations in the number of load-throughput testing packages, namely 1 byte to 255 bytes, and the number of packages in the range-test is 1 byte to 84 bytes. Loss packages are detected at a distance of 400 meters. The results of the analysis of throughput, distance and size of the package do not really affect the performance of XBee S2C data transmission. Pearson test results on throughput produce the highest value of 0.961231 (delivery with a distance of 10 meters), and the lowest yield is -0.96648 (delivery with a distance of 150 meters Pearson field test results on maximum Range-test were valued at 0.863349 at 300 meters test and a minimum value of -0.87328 at a distance of 300 meters. The range of the test range greatly affects the RSSI produced. However, the data sent remains stable from a distance of 10 meters to 300 meters with an average of 80-90% of data successfully sent, and new connections will be lost at a distance of 400 meters.